Saat-Saat Penting: Pengalaman Berharga dalam Proker KKN Memandikan dan Mengafani Jenazah - Chaidar, Muhammad Raihan (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2024)
Death is an inevitable event in the lives of all creatures, including humans. Regardless of when and how death occurs, the responsibility for handling a deceased individual becomes crucial for those who are still alive. Religion, especially Islam, provides comprehensive guidelines on how to deal with the deceased. However, in everyday life, many Muslims are not well-versed in the proper procedures for conducting funerals in accordance with their religious teachings.This article outlines the importance of understanding the procedures for managing funerals, considering aspects such as religious and cultural significance, paying final respects, complying with legal and administrative requirements, ensuring hygiene and health considerations, providing psychological support, preparing in advance, and maintaining efficiency and organization. Funeral management can be categorized as a collective duty known as